Smart pigeonhole system by sending notification through short messagging system - Nazariah, Abdullah (2015)
Smart pigeonhole system by sending notification through short messaging system is a system that have been built for resident to get a notification about arriving mail through short messaging system in their phone. This system allows residents to save their time rather than always check the existence of the letter in their mailbox if residents living in high buildings. During development of this system, a method called the system development life cycle was used to gather information. This system has five phases: namely, planning, analysis, implementation, design and testing. This system is essential to ensure product quality and ensure a trip in the implementation of projects always run smoothly. The system is constructed using several components including infrared sensors, ultrasonic sensors and arduino yun. Infrared sensors used to detect the presence of the mail into the box while the ultrasonic sensor is used to detect the level of fullness of the mailbox. If the level is above a letter in the set, the residents will receive a message in order that the whole situation and asked that residents take their mail in circumstances immediately. In conclusion, this system is very useful to residents to enable them to get a warning about the mail that came into their mailbox.